Why women's entrepreneurial activities are low in China? The psychological perspective of self-esteem. Issue 1 (31st December 2023) - Li, Zhongwu; Lu, Fengzhi; Feng, Xueliang
Abstract: How to increase women's entrepreneurial activities and expand the proportion of female entrepreneurs among entire entrepreneurs has been the long-term focus of scholars. For the first time, this article uses the China Family Panel Studies (CFPS) and the National Survey on Women's Social Status of China (NSWSS) to study why women's entrepreneurial activities are relatively low in China from the psychological perspective of self-esteem. After controlling for related variables, the regression results show that self-esteem has a positive effect on women's entrepreneurial activities. It indicates that the relatively low entrepreneurial activities of women are partially attributed to their low level of self-esteem. In addition, compared with cognitive ability and 'The Big Five' non-cognitive ability, self-esteem plays a greater role in explaining women's entrepreneurial activities. While using propensity score matching and instrument variable methods to deal with the self-selection bias and endogenous problem of self-esteem, the results corroborate the conclusion. Further analysis indicates that social capital and risk-taking attitudes are two important mechanisms for self-esteem to influence women's entrepreneurial activities. The attempt to incorporate the unique psychological trait of self-esteem into female entrepreneurship sheds light on the interdisciplinary research, and provides a new path for improving women's entrepreneurial activities.